Development of a silver ion-based water purifier - Ragusa, Paul J. (Kansas State University, 2010)
Abstract Water purification methods that remove pathogens and harmful or distasting molecules make water potable. Recently, silver loaded ion-exchange resins have demonstrated a strong role in removing microbes. The goal is to make an effective silver ion-based water purifier that is portable, environmentally stable, and cost efficient. The project was conducted as a collaborative effort with Safewater A/S, an up and coming entrepreneurial business located in Denmark that is interested in developing novel water purifiers for developing nations, adventurers and military personnel. Purolite, a prominent business in ion-exchange resins located in Whales, designed and provided Safewater A/S and our research team with experimental resins for water purification, which will be discussed in the body of this thesis. The data reveals critical issues that may render this tool unavailable for commercial production in some countries due to the mode of action for killing the bacteria and the amount of silver leaching. Tests were conducted using Escherichia coli K12 and Enterococcus faecalis OG1SSp as model fecal organisms using different silver ion-exchange resins. Surveillance of leached silver ions, pH changes, and total dissolved solids (TDS) were also monitored to find correlations with capacity (liters of purified water produced) and effectiveness of microbicidal action. Overall, one resin was found to contain properties consistent with the stated objectives; however its use in some countries as a water purifier for human consumption will be nullified due to extensive silver leaching. Although this resin could be used in the United States of America since it passes the Environmental Protection Agency (EPA) standards, Safewater A/S is interested in further developing it for countries with stricter regulatory constraints before mass production. The goal of the present thesis report is to address the stated objectives in the development of a water purifier.
Keywords: Silver resin; Water purifier; Silver ion-exchange; Biocidal resin; Biology, General (0306); Biology, Microbiology (0410); Chemistry, Physical (0494)